Job Variables and Work Re-Adjustment Among Repatriates: The Moderating Role of Social Support (Journal of International Studies, 2020)
The objective of this paper is twofold. Firstly, to determine the relationship between job variables (role clarity, role discretion, role conflict, and role novelty) on work re-adjustment among repatriates. Secondly, is to test the moderating effect of social support on the relationship between job variables and work re-adjustment. Analyses of 104 repatriates using multiple regression analysis revealed that all job variables did not show relationship with work re-adjustment as hypothesized. However, it was found that social support is able to moderate the relationship between role discretion and work re-adjustment. Implications of the finding and areas for future research are discussed.